3D Nanostructured Conjugated Polymers for Optical Applications. (19th October 2015) - Dehmel, Raphael; Nicolas, Alexandre; Scherer, Maik R. J.; Steiner, Ullrich
Abstract : The self assembly of block‐copolymers into the gyroid morphology is replicated into 3D nanostructured conjugated polymers. Voided styrenic gyroidal networks are used as scaffolds for the electrodeposition of two poly(3, 4‐ethylenedioxythiophene) derivatives and poly(pyrrole). The careful choice of solvents and electrolytes allows the excellent replication of the initial self‐assembled morphology into self‐supporting gyroidal conjugated polymer networks. The nanostructured films are employed to fabricate electrochromic devices, exhibiting excellent color contrast upon switching, with fast switching speeds. The versatility and reliability of this method are demonstrated by the creation of switchable Fresnel zone plates, with which the focussing of light can be switched on and off. Abstract : Mesoporous networks of conjugated polymers were synthesized by electropolymerisation into templates created by block‐copolymer self‐assembly. The nanostructured conductive polymer layers were employed to manufacture electrochromic zone‐plates that reversibly switch on and off the focussing of light.